2015
DOI: 10.4172/2155-9929.1000241
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Alpha Lipoic Acid against Phenytoin Induced Behavioral Abnormalities in Rats

Abstract: IntroductionEpileptic disorders affect approximately 0.5-1% of human population [1]. The main goal in the treatment of epilepsy is to attain a complete control over seizures without potential side effects to improve the quality of life. Phenytoin is a most common and effective antiepileptic drug (AED) prescribed for a prolonged period to achieve seizure control in all types of generalized as well as partial seizures and status epilepticus [2]. Phenytoin causes several serious side effects notably neurotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Previously, Nádia et al (2018) found that ALA 200 mg/kg reversed the deficits in short-term memory in CORT-induced depressive-like behaviour and cognitive deficits using NORT. Furthermore, Saraswathy et al (2015) found that, in a dose-dependent fashion, ALA (at doses 50, 100 and 200 mg/kg) reversed phenytoin-induced memory impairment of rats subjected to the elevated plus-maze test. The possible mechanism might be the prevention of alterations in insulin signalling, thereby decreasing memory impairment by increasing vesicular glutamate transporter 1 (VGlut 1), which was found impaired in the frontal regions of HFF Alzheimer's rats with a decline in cognition (Rodriguez-perdigon et al, 2016).…”
Section: Catalasementioning
confidence: 94%
“…Previously, Nádia et al (2018) found that ALA 200 mg/kg reversed the deficits in short-term memory in CORT-induced depressive-like behaviour and cognitive deficits using NORT. Furthermore, Saraswathy et al (2015) found that, in a dose-dependent fashion, ALA (at doses 50, 100 and 200 mg/kg) reversed phenytoin-induced memory impairment of rats subjected to the elevated plus-maze test. The possible mechanism might be the prevention of alterations in insulin signalling, thereby decreasing memory impairment by increasing vesicular glutamate transporter 1 (VGlut 1), which was found impaired in the frontal regions of HFF Alzheimer's rats with a decline in cognition (Rodriguez-perdigon et al, 2016).…”
Section: Catalasementioning
confidence: 94%